2015
DOI: 10.1136/jclinpath-2015-203066
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cell-line-derived xenograft tumours as controls for immunohistochemical testing for ER and PR

Abstract: Quality control (QC) for immunohistochemistry (IHC) analysis routinely incorporates archived specimens for on-slide control material. We have assessed the utility of cell-line-derived xenograft (CDX) tumours for QC in breast estrogen receptor (ER) and progesterone receptor (PR) biomarker testing. Immunoblot and IHC analyses were used to select cell lines with different steady-state levels of ER and PR expression. CDX tumours all demonstrated consistent and comparable expression of ER and PR with corresponding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 10 publications
(9 reference statements)
1
7
0
Order By: Relevance
“…MCF7 cells express high levels of ER,12 and as expected, MCF7 breast cancer CDX tumours consistently demonstrated strong expression of ER under standard preanalytical processing (10% NBF for 24 hours at RT). To assess the effects of variable FT on ER scoring, MCF7 CDX tumours were fixed for periods from 1 hour to 120 hours.…”
Section: Resultssupporting
confidence: 72%
See 3 more Smart Citations
“…MCF7 cells express high levels of ER,12 and as expected, MCF7 breast cancer CDX tumours consistently demonstrated strong expression of ER under standard preanalytical processing (10% NBF for 24 hours at RT). To assess the effects of variable FT on ER scoring, MCF7 CDX tumours were fixed for periods from 1 hour to 120 hours.…”
Section: Resultssupporting
confidence: 72%
“…Previously, we demonstrated that CDX tumours were suitable as homogenously expressing models that were reproducible, yet indistinguishable from tumour specimens submitted for biomarker reporting 12. Tumour cores were arranged on a microarray and blind-scored by all observers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several transgenic or knockout models for extra-uterine Müllerian/ovarian and for mammary carcinomas have been developed over the last 2 decades (see ( Pfefferle et al, 2013 , Hollern and Andrechek, 2014 , Hasan et al, 2015 ) for reviews). In some cases, specific pathways, including Her-2/neu in mammary epithelium, Pten in Müllerian epithelium, and others have been targeted while others have focused on Brca1 / 2 inactivation in tissues corresponding to those with an elevated cancer risk in human BRCA1 / 2 mutation carriers.…”
Section: Discussionmentioning
confidence: 99%